PERTUMBUHAN EKONOMI INDONESIA SEBELUM DAN SESUDAH PEMBERLAKUAN MEA - Intan Roosdiantoro; Ahmad Zafrullah TN.; Firman Rosjadi Djoemadi (Perpustakaan Universitas Surabaya, 2020)
This study explains about the conditions of Indonesia's Economic Growth before and after the enactment of the ASEAN Economic Community (AEC). This research uses qualitative descriptive approach by using qualitative descriptive analysis. In addition to focus on the conditions of Indonesia's Economic Growth before and after the enactment of the MEA, this research will also explain about one of the issues which related to Indonesia's Economic Growth before and after the MEA's implementation. The issue is about the cause of the low competitiveness of the Indonesian economy to Singapore, Malaysia and Thailand before and following the enactment of the ASEAN Economic Community (AEC). The findings of this study indicate that Indonesia's Economic Growth before and after the enactment of the ASEAN Economic Community (AEC) is in a different, volatile, and fairly stable condition. When compared, after the implementation of AEC Indonesia's Economic Growth has decreased. It shows that, AEC has no positive impact on Indonesia Economic Growth. There are various factors that cause it one of them is the significant impact of the AEC can not be seen in the short term but in the long run. Even if Indonesia's Economic Growth is stable, there are various problems that occur and potentially adversely affect Indonesia's Economic Growth. The low competitiveness of the Indonesian economy against Singapore, Malaysia and Thailand is due to the ongoing domestic problems that hamper Indonesiacompetitiveness in the globalized world. These problems include the low ease of licensing and doing business, infrastructure problems, and bureaucratic issues.